Impacts and effects of a demerger process on morale of technical employees of a South African engineering consulting firm - Hafane, Matete Sarah (My University, 2021)
Human capital issues are often overlooked during a demerger process and this can harm employee morale. The study intends to demonstrate how employee morale can be affected by the demerger process and how important it is a successful demerger. A descriptive research design that followed a survey strategy was adopted to satisfy the objectives of the study in addition to the literature review. The population for this study was technical employees of a South African engineering consulting firm with a size of 112 employees. The collected data was analysed using Statistical Package for the Social Sciences (SPSS) and presentation of the study results was done in the form of bar and pie charts, and percentages. It was found the demerger process can negatively affect employee moral because it can result in factors such as stressful work environment, talent turnover, job satisfaction, retrenchments, and anxiety-related stress that influence employee morale negatively. However, it was found in general the demerger process positively affected employee morale which is unusual for demergers. It is, therefore recommended that further studies be carried out on other companies to determine the most contributing factor during the demerger that can keep employee morale positive
A research report submitted to the School of Mechanical, Industrial, Aeronautical Engineering, Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2021